Proliferation and Osteogenic Differentiation of Mesenchymal Stem Cells Induced by a Short Isoform of NELL‐1. (17th February 2015) - Pang, Shen; Shen, Jia; Liu, Yi; Chen, Feng; Zheng, Zhong; James, Aaron W.; Hsu, Ching-Yun; Zhang, Hong; Lee, Kevin S.; Wang, Chunling; Li, Chenshuang; Chen, Xuepeng; et al.
Abstract: Neural epidermal growth factor‐like (NEL)‐like protein 1 (NELL‐1) has been identified as an osteoinductive differentiation factor that promotes mesenchymal stem cell (MSC) osteogenic differentiation. In addition to full‐length NELL‐1, there are several NELL‐1 ‐related transcripts reported. We used rapid amplification of cDNA ends to recover potential cDNA of NELL‐1 isoforms. A NELL‐1 isoform with the N‐terminal 240 amino acid (aa) residues truncated was identified. While full‐length NELL‐1 that contains 810 aa residues (NELL‐1810 ) plays an important role in embryologic skeletal development, the N‐terminal‐truncated NELL‐1 isoform (NELL‐1570 ) was expressed postnatally. Similar to NELL‐1810, NELL‐1570 induced MSC osteogenic differentiation. In addition, NELL‐1570 significantly stimulated MSC proliferation in multiple MSC‐like populations such as murine C3H10T1/2 MSC cell line, mouse primary MSCs, and perivascular stem cells, which is a type of stem cells proposed as the perivascular origin of MSCs. In contrast, NELL‐1810 demonstrated only limited stimulation of MSC proliferation. Similar to NELL‐1810, NELL‐1570 was found to be secreted from host cells. Both NELL‐1570 expression lentiviral vector and column‐purified recombinant protein NELL‐1570 demonstrated almost identical effects in MSC proliferation and osteogenic differentiation, suggesting that NELL‐1570 may function as a pro‐osteogenic growth factor. In vivo, NELL‐1570 induced significant calvarial defect regeneration accompanied by increased cell proliferation. Thus, NELL‐1570 has the potential to be used for cell‐based or hormone‐based therapy of bone regeneration. Stem Cells 2015;33:904–915